Bird Commmunity in Bagek Kembar Mangrove Essential Ecosystem Area (EEA), Sekotong, West Lombok - Manisa, Safariyanti; Hadiprayitno, Gito; Suyantri, Eni (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Birds are wildlife found in many habitats, such as beaches, swamps, mountains and lowlands. This study aims to determine the bird community in the Bagek Kembar essential ecosystem area, West Lombok Regency. Data was collected using the transect path method (exploration) and point count. The research was conducted in November-December. Observation was carried out in the morning at 06.30- 09.30 and in the afternoon at 15.30-18.30 Central Indonesian Time (GMT +8) with representatives of 3 observation locations: pond area, rehabilitation mangrove and natural mangrove. Data collection was done using transect lines (cruising) and point count. The results showed that there were 57 bird species from 23 families categorised into migratory birds (18 species), protected birds (12 species), and six species of birds categorised as NT (Near Threatened). The results of the abundance index of species included in the highest dominant category are Cerulean Kingfisher (Alcedo coerulescens), with a value of 7.87% found in the pond area. Furthermore, the results of the diversity index of the three areas have a high diversity index value of 3.900.